Comparative Analysis of the Efficiency of Medicinal Plants for the Treatment and Prevention of COVID-19 - Kamkin, Viktor; Kamarova, Aidana; Shalabayev, Baurzhan; Kussainov, Assyltas; Anuarbekov, Marat; Abeuov, Serik (International Journal of Biomaterials, 2022)
The COVID-19 pandemic has once again prompted people to resort to the remedies of folk and alternative medicine. Medicinal plants, because of their chemical composition, pharmacological properties, and the action of biologically active substances, can stop and relieve the symptoms of the disease. The purpose of the work is a comparative flora analysis of medicinal plants to identify the most prospective plant and further production of a remedy for the avoidance, treatment, and rehabilitation of COVID-19. The search for prospective medicinal plants was performed by analyzing the literature in online databases: Web of Science, Scopus, Google Scholar, and PubMed, including official WHO media sites. According to recent studies related to COVID-19, a significant number of medicinal plants with anti-inflammatory, antiviral, and immunostimulatory effects have been identified. A comparative study of nine medicinal plants was conducted to determine the most suitable medicinal plant to treat coronavirus infection. According to the results of the comparative analysis, Chamaenerion angustifolium Seg. showed itself as the most prospective medicinal plant with the greatest pharmacological effect compared with other types of medicinal plants. Its therapeutic properties allow physiological relief of 18 symptoms of coronavirus infection. It is advisable to conduct further clinical trials for the treatment and rehabilitation of COVID-19 using preparations from this plant.